A kid's guide to anime & manga : exploring the history of Japanese animation and comics - Sattin, Samuel; Macias, Patrick, 1972- (RP Kids, 2023)
"An accessible, inclusive guide aimed at helping young fans celebrate their okatu spirit by sharing the history of anime and manga while giving young readers advice on how to explore and interact with this fandom. Whether they're watching anime on Netflix and Crunchyroll or bringing home stacks of manga from the library or bookstore, there is no denying that young fans need a guidebook to help them navigate this geeky space. Written by anime and manga fans, writers, and reviewers Samuel Sattin and Patrick Macias, A Kid's Guide to Anime & Manga includes chapters on: History and importance of anime and manga; Breakdowns of how anime and manga are made; Recommendations of popular series and films to enjoy; Pro-tips on how to create your own anime and manga and to be involved in cosplay communities. A Kid's Guide to Anime & Manga is packed with eye-catching two-color illustrations, fascinating facts, inspiring interviews, a glossary, and more to help young fans navigate and contribute to the growing anime and manga space"--